Comparison of Surface-Enhanced Raman Scattering Properties of Serum and Urine for the Detection of Chronic Kidney Disease in Patients. Issue 4 (April 2021) - Zong, Ming; Zhou, Lan; Guan, Qiunong; Lin, Duo; Zhao, Jianhua; Qi, Hualin; Harriman, David; Fan, Lieying; Zeng, Haishan; Du, Caigan
Chronic kidney disease (CKD) affects more than 10% of the global population and is associated with significant morbidity and mortality. In most cases, this disease is developed silently, and it can progress to the end-stage renal failure. Therefore, early detection becomes critical for initiating effective interventions. Routine diagnosis of CKD requires both blood test and urinalyses in a clinical laboratory, which are time-consuming and have low sensitivity and specificity. Surface-enhanced Raman scattering (SERS) is an emerging method for rapidly assessing kidney function or injury. This study was designed to compare the differences between the SERS properties of the serum and urine for easy and simple detection of CKD. Enrolled for this study were 126 CKD patients (Stages 2–5) and 97 healthy individuals. SERS spectra of both the serum and urine samples were acquired using a Raman spectrometer (785 nm excitation). The correlation of chemical parameters of kidney function with the spectra was examined using prinicpal component analysis (PCA) combined with linear discriminant analysis (LDA) and partial least squares (PLS) analysis. Here, we showed that CKD was discriminated from non-CKD controls using PCA–LDA with a sensitivity of 74.6% and a specificity of 93.8% for the serum spectra, and 78.0% and 86.0 % for the urine spectra. The integration area under the receiver operating characteristic curve was 0.937 ± 0.015 ( p < 0.0001) for the serum and 0.886 ± 0.025 ( p < 0.0001) for the urine. The different stages of CKD were separated with the accuracy of 78.0% and 75.4% by the serum and urine spectra, respectively. PLS prediction (R 2 ) of the serum spectra was 0.8540 for the serum urea ( p < 0.001), 0.8536 for the serum creatinine ( p < 0.001), 0.7500 for the estimated glomerular filtration rate (eGFR) ( p < 0.001), whereas the prediction (R 2 ) of urine spectra was 0.7335 for the urine urea ( p < 0.001), 0.7901 for the urine creatinine ( p < 0.001), 0.4644 for the eGFR ( p < 0.001) and 0.6579 for the urine microalbumin ( p < 0.001). In conclusion, the accuracy of associations between SERS findings of the serum and urine samples with clinical conclusions of CKD diagnosis in this limited number of patients is similar, suggesting that SERS may be used as a rapid and easy-to-use method for early screening of CKD, which however needs further evaluation in a large cohort study.